The impact of financial sustainability on Iraq’s economic growth for the period (2004-2022) - Mohammad, Warhel S.; Ahmed, Dildar H. (Humanities Journal of University of Zakho, 2024)
The current study aims to estimate the impact of some financial sustainability indicators measured by (public debt, oil revenues, government spending, interest rates, inflation, exchange rate) on economic growth as measured by (gross domestic product) in Iraq for the period (2004-2022). The study used the quantitative method using the autoregressive distributed lag model (ARDL) to estimate the parameters of the variables used for financial sustainability. The results of the study showed that the variables of financial sustainability have a significant impact on the economic growth of Iraq during the period (2004-2022), the results of the study showed the existence of a long-term equilibrium relationship. Between financial sustainability and economic growth, as oil revenues are considered one of the most important financial sustainability variables that have an impact on economic growth, followed by the government spending variable, then the exchange rate variable comes in third importance, followed by the total public debt variable, and finally the inflation rate variable. While the significant effect of the interest rate variable on economic growth in the long term did not appear, the study proposes a set of proposals, the most important of which is rationalizing government spending and focusing on investment spending in order to generate additional income in the future and thus increase the probability of financial sustainability, and find additional sources of financing from economic sectors. Vital areas in Iraq, such as agriculture and industry, and reducing total dependence on oil revenues through a strategic plan to diversify revenue sources, as most Gulf Cooperation Council countries have done.